1988
DOI: 10.1111/j.1365-2362.1988.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypercalcaemia in a health survey: a 14‐year follow‐up study of serum calcium values

Abstract: Among 16,401 subjects attending two health screenings, in 1969 and 1971, 176 showed hypercalcaemia on both occasions, i.e. serum calcium values above 2.60 mmol l-1. The prevalence of hypercalcaemia increased in women with advancing age and occurred in close to 3% of those above the age of 60, whilst in men it was found in less than 0.7% in all age groups. The mean serum calcium concentration in women above the age of 50 was significantly higher than in men. This observation could at least partly explain why hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
6

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(89 citation statements)
references
References 30 publications
1
82
0
6
Order By: Relevance
“…et al (5). Mean follow-up time was greater than 10 years in three of these studies (1,6,12), and 8.2 years in one (5). In the remaining it was 3.5 -5.6 years (2 -4), which might not suffice for forming an opinion.…”
Section: Discussionmentioning
confidence: 99%
“…et al (5). Mean follow-up time was greater than 10 years in three of these studies (1,6,12), and 8.2 years in one (5). In the remaining it was 3.5 -5.6 years (2 -4), which might not suffice for forming an opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies limiting the subject population to retirees or females 55 to 75 years of age detected a prevalence of about 2% (see Table I). The lower age limit in the Tromsö, Gävle, and Stockholm [9,10,12] studies was 20 Á25 years while the rate in Tibro was calculated for a population aged 7 years and older, as this was the age of the youngest patient with hypercalcaemia. With a lower age limit of 45 years, a rate of 0.43% would have been registered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To detect more patients with pHPT, the Swedish authorities encouraged an increase in serum calcium analyses in primary care [8]. In the majority of patients serum calcium levels remain stable over decades [9,10], but in a small proportion Correspondence: Sofia Dalemo, Guldvingens Health Care Centre, Ö stbygatan 21 Á23, SE-531 37 Lidkö ping, Sweden. E-mail: sofia.dalemo@vgregion.se…”
mentioning
confidence: 99%
“…The incidence and severity of this renal impairment vary considerably among reports, probably due to both the heterogeneity of the patient samples studied and the different techniques used for estimating renal function. Several authors who monitored plasma creatinine levels in pHPT patients reported that renal function might remain normal despite long-standing hypercalcemia (11,12).…”
Section: Discussionmentioning
confidence: 99%